Enhancement in Seed Priming-Induced Starch Degradation of Rice Seed Under Chilling Stress via GA-Mediated α-Amylase Expression - Lixiao Nie; Shaokun Song; Qi Yin; Tingcheng Zhao; Hongyan Liu; Aibin He; Weiqin Wang (Rice, 2022)
Abstract Chilling stress is the major abiotic stress that severely limited the seedling establishment of direct-seeded rice in temperate and sub-tropical rice production regions. While seed priming is an efficient pre-sowing seed treatment in enhancing crop establishment under abiotic stress. Our previous research has identified two seed priming treatments, selenium priming (Se) and salicylic priming (SA) that effectively improved the seed germination and seedling growth of rice under chilling stress. To further explore how seed priming enhance the starch degradation of rice seeds under chilling stress, the present study evaluated the effects of Se and SA priming on germination and seedling growth, α-amylase activity, total soluble sugar content, hormone content and associated gene relative expression under chilling stress. The results showed that both Se and SA priming significantly increased the seed germination and seedling growth attributes, and enhanced the starch degradation ability by increasing α-amylase activity and total soluble sugar content under chilling stress. Meanwhile, seed priming increased the transcription level of OsRamy1A, OsRamy3B that regulated by GA, and increased the transcription level of OsRamy3E that regulated by sugar signals. Furthermore, seed priming significantly improved the GA3 contents in rice seeds by up-regulating the expression of OsGA3ox1 and OsGA20ox1, and decreased the ABA content and the expression of OsNCED1, indicating that the improved starch degradation ability in primed rice seeds under chilling stress might be attributed to the increased GA3 and decreased ABA levels in primed rice seeds, which induced the expression of GA-mediated α-amylase. However, studies to explore how seed priming mediate hormonal metabolism and the expression of OsRamy3E are desperately needed.